Avaliação das propriedades de forma de agregados utilizados em lastro ferroviário a partir do uso do processamento digital de imagens - Diógenes, Daianne Fernandes (2016)
The ballast layer is responsible for supporting the railway superstructure, being repeatedly charged and discharged by the passage of trains. The aggregates shape properties and the particle size thereof may be directly affected by many factors such as: track usage time, clogging of thinner materials and maintenance processes performed primarily through the tamping, causing breakage and wear in these materials. The validation indices used to evaluate shape, angularity and texture are used to understand the interaction of these materials at various stages of the railway, such as in cases of primary and secondary crushing of the aggregates before and after the completion of the tamping ballast, at the beginning of the service life and after a certain service period. This study aims to evaluate the influence of the aggregates’ shape properties that make up the ballast layer in the operation and performance of the structure with the use of Digital Image Processing (DIP), the Aggregate Image Measurement System (AIMS) tool was applied to the study. Research involving the evaluation of ballast requires large-scale equipment to conduct triaxial tests, in order to obtain resilient modulus and resistance to permanent deformation, Thus, the offset technique, translation of the gradation curve from the original size distribution curve, was used in this study to evaluate the material used in the ballast scaled. It was verified, by traditional methodologies, that the aggregates collected in the permanent route obtained higher percentage of cubic particles when compared to the ballast material (initial phase), being related to the breakage of the flat-elongated particles due to the loads from wagons and boards, the maintenance with vibrating blades, the friction between particles and the impacts of materials disposal. Regarding the DPI characterization, the initial ballast presented particles with low roughness differently from the materials collected in the permanent way, presenting smooth surface texture. Materials from the track presented better mechanical behavior compared to the initial ballast, being attributed to the higher percentage of cubic particles of smaller sizes, as well as to the granulometric curve with more dense characteristics. This way, it is possible to conclude, regarding stability and strength, that the material just below the sleepers and the one with 5 years in service were less impacted, presenting smaller deformations compared to the initial ballast materials. However, they may be unfavorable in one of the main functions of the ballast layer, the drainage.